The Impact of Digital Marketing on Export Sustainability in the Digital Era - Saputra, Bayu Anindito; Zawawi (Business and Investment Review, 2023)
Digital marketing has become a key element in understanding and shaping export sustainability in the digital era. This research aims to explore the impact of digital marketing on export sustainability in the context of the current digital era. With rapid digital transformation, companies and exporting countries need to understand how digital marketing can impact various aspects of export sustainability, including economic growth, operational efficiency and environmental sustainability. This research uses qualitative methods and uses a literature study approach related to digital marketing, exports and sustainability. Literature findings provide insight into how digital marketing can accelerate global market penetration, increase supply chain efficiency, and make a positive contribution to the sustainability aspects of exports. The results of this research demonstrate that implementing digital marketing strategies can open up new opportunities to increase competitiveness and export growth. Positive impacts are also seen in increasing brand awareness, strengthening relationships with global consumers, and adapting to international market trends. However, challenges such as data security, international regulatory compliance, and changing digital consumer behavior have also emerged as critical factors that can impact export sustainability. Therefore, this research provides a holistic understanding of the relationship between digital marketing and export sustainability, providing a foundation for companies and government policies to optimize digital potential in facing global challenges and achieving sustainable export sustainability.